A brighter dawn [large type] - Gould, Leslie, 1962- (Amish Memories, 2023)
"Ivy Zimmerman is successfully navigating her life as a young Mennonite woman, one generation removed from her parents' Old Order Amish upbringing. But when her parents are killed in a tragic accident, Ivy's way of life is upended. As she deals with her grief, her younger sisters needs, her relationship with her boyfriend, and her Dawdi and Mammi's strict rules, Ivy finds solace in both an upcoming trip to Germany for an international Mennonite youth gathering and in her great-great-aunt's story about Clare Simons, another young woman who visited Germany in the late 1930s. As Ivy grows suspicious that her parents' deaths weren't, in fact, an accident, she gains courage from what she learns of Clare's time in pre World War II Germany. With the encouragement and inspiration of the women who have gone before her, Ivy seeks justice for her parents, her sisters, and herself."--